2010
DOI: 10.4097/kjae.2010.59.6.411
|View full text |Cite
|
Sign up to set email alerts
|

Rocuronium bromide induced anaphylaxis in a child -A case report-

Abstract: Anaphylaxis or anaphylactoid reaction in pediatric patient during anesthesia is rare. We report a rocuronium induced anaphylactic reaction in a 33-month-old female. The patient was scheduled to undergo escharectomy due to injuries suffered from a major burn. Shortly after administration of rocuronium, the patient developed severe hypotension, tachycardia, and hypoxia. A similar reaction occurred after administration of rocuronium on subsequent anesthesia. She underwent uneventful anesthesia with volatile induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Several epidemiological studies and case reports about rocuronium and anaphylaxis have been reported up until today [4]- [7]. However, rocuronium-induced anaphylaxis in infants must be very rare because we cannot easily find it in the public databases.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies and case reports about rocuronium and anaphylaxis have been reported up until today [4]- [7]. However, rocuronium-induced anaphylaxis in infants must be very rare because we cannot easily find it in the public databases.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative anaphylactic reaction is a rare but life-threatening complication [1][2][3][4][5]. Nearly all kinds of medications and substances used in anesthesia and surgery can cause anaphylaxis, including hypnotic opioids, local anesthetics, colloids, dyes, antibiotics, neuromuscular blocking agents (NMBAs), disinfectants, and latex [4].…”
Section: Introductionmentioning
confidence: 99%